Doing the Corporate Business with Piercing the Corporate Veil Doctrine: Indonesia, Us And Uk Perspective - Ng Catharina Enggar Kusuma; Fl. Yudhi Priyo Amboro (Fakultas Hukum, Universitas Warmadewa, 2020)
The absence of piercing the corporate veil doctrine in the Indonesian company law shows that the subsidiaries of such corporate groups are considered a separate legal personality, hence it is probably almost impossible to held the parent company liable for its subsidiaries’ legal actions under any conditions. This research adopted a normative legal research with a comparative law study method. The goal of this research is describe the implementation of piercing the corporate veil doctrine in Indonesia, US and UK, then to make the points of contribution of this doctrine to be regulated properly in Indonesia. In fact, piercing the corporate veil doctrine is implemented in Indonesia, although there was not any normative legal basis of the doctrine itself, whereas in US and UK, the doctrine is implemented and further developed through precedents. Therefore, since there is an evident relationship between a parent company and its subsidiary, whereby in certain cases the parent company can and should be held liable for the acts of its subsidiary, there should be a more explicit regulation regarding both corporate groups and piercing the corporate veil doctrine.